Irreversibility analysis of a bioconvective two-phase nanofluid in a Maxwell (non-Newtonian) flow induced by a rotating disk with thermal radiation - Ali Farhan; Zaib Aurang; Khan Umair; Ahmed Muhammad Faizan; Zafar Syed Sohaib; Elattar Samia (Open Physics)
This analysis examined the convective heat transport influence of stagnant point bioconvection movement of a Darcy–Forchheimer flow past a rotating disk with entropy generation analysis. The energy expression is contributed by the effect of thermal radiation and the heat generation/absorption rate. The second law analysis also accounted for the given study’s inspection of the irreversible analysis. The Buongiorno nanoscale model simulates the Brownian movement and thermophoretic effect. Also, the Maxwell fluid model is used for non-Newtonian rheological characteristics, and a Darcy–Forchheimer flow model is used for the porous medium. The nonlinear model equations are transformed into dimensionless equations through an appropriate transformation. Further, the converted expressions were computed using the homotopic procedure. Moreover, the graphs illustrate the consequences of flow variables on microorganism profile density, concentration distributions, thermal, velocity, entropy, and the Bejan number. The inertia coefficient and non-Newtonian fluid variable reveal the significance of axial and radial velocity decrease. An enhancement in the thermal field is noted for the higher values of the radiation parameter and the Biot number. The larger magnitude of the Brinkman number escalates the rate of entropy and the Bejan number. The drag force decreased from 7.95 to 7.13% for the values of the inertia coefficient. Heat transport is enhanced by 22% as the larger magnitude of thermal radiation parameter (Rd{\rm{Rd}}) rises. Mass transfer is further enhanced by bioconvection, which increases nanoparticle dispersion by up to 18%.